2008
DOI: 10.1002/bit.21933
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic methanethiol degradation and methanogenic community analysis in an alkaline (pH 10) biological process for liquefied petroleum gas desulfurization

Abstract: Anaerobic methanethiol (MT) degradation by mesophilic (30 degrees C) alkaliphilic (pH 10) communities was studied in a lab-scale Upflow Anaerobic Sludge Bed (UASB) reactor inoculated with a mixture of sediments from the Wadden Sea (The Netherlands), Soap Lake (Central Washington), and Russian soda lakes. MT degradation started after 32 days of incubation. During the first 252 days, complete degradation was achieved till a volumetric loading rate of 7.5 mmol MT/L/day, and sulfide, methane, and carbon dioxide we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 31 publications
1
15
2
Order By: Relevance
“…The interesting possibility of niche differentiation among methylotrophic methanogens due to competition for C 1 substrates in the extreme Lonar Lake environment needs further exploration. 16S rRNA gene sequences related to M. oregonensis have been retrieved by PCR-DGGE fingerprint analysis of methanethiol (MT) degrading communities in a UASB reactor (pH-10) inoculated with sediments from the Wadden Sea (Netherlands), Soap Lake (USA), and Russian soda lakes (van Leerdam et al, 2008). Methanolobus-related phylotypes in the Lonar Lake environment could be dependent on methanol and other C 1 substrates that are derived from the decomposition of cyanobacterial mats that extend across surface layers of the water column (Surakasi et al, 2010) and/or dead plant matter (Warneke et al, 1999).…”
Section: Characterization Of Active Methylotrophic Archaeamentioning
confidence: 99%
“…The interesting possibility of niche differentiation among methylotrophic methanogens due to competition for C 1 substrates in the extreme Lonar Lake environment needs further exploration. 16S rRNA gene sequences related to M. oregonensis have been retrieved by PCR-DGGE fingerprint analysis of methanethiol (MT) degrading communities in a UASB reactor (pH-10) inoculated with sediments from the Wadden Sea (Netherlands), Soap Lake (USA), and Russian soda lakes (van Leerdam et al, 2008). Methanolobus-related phylotypes in the Lonar Lake environment could be dependent on methanol and other C 1 substrates that are derived from the decomposition of cyanobacterial mats that extend across surface layers of the water column (Surakasi et al, 2010) and/or dead plant matter (Warneke et al, 1999).…”
Section: Characterization Of Active Methylotrophic Archaeamentioning
confidence: 99%
“…Haloalkaline microorganisms have also been proposed to be applied in the production of biofuels such as hydrogen and ethanol (Zhao et al, 2014 ). Van Leerdam et al ( 2008 ) showed that it was possible to use a haloalkaline consortium to produce biogas under controlled conditions. The ability of haloalkaline bacteria and archaea to live in alkaline environments could be exploited to produce biogas rich in methane.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the potential to convert methane thiol and dimethyl sulfide to sulfide is shown for the moderately halophilic methanogen Methanohalophilus, but without any detailed study on salt influence of the process (Ni and Boone, Downloaded by [Stanford University Libraries] at 04:43 03 October 2012 1993). Recently, the same potential has been demonstrated for haloalkaline conditions in a bioreactor inoculated with the soda lake sediments containing Methanolobus taylorii as a dominant organism (van Leerdam et al, 2008a;van Leerdam et al, 2008b).…”
Section: Bioconversion Of Toxic Inorganic Compounds Relevant To Oil-gmentioning
confidence: 75%